Enhancing proteasome activity by NMDAR antagonists explains their therapeutic effect in neurodegenerative and mental diseases - Fikret Sahin; Aslihan Gunel; Buse Turegun Atasoy; Ulku Guler; Bekir Salih; Isinsu Kuzu; Mehmet Taspinar; Ozgur Cinar; Selda Kahveci (Scientific Reports)
Abstract NMDAR antagonists, such as memantine and ketamine, have shown efficacy in treating neurodegenerative diseases and major depression. The mechanism by which these drugs correct the aforementioned diseases is still unknown. Our study reveals that these antagonists significantly enhance 20S proteasome activity, crucial for degrading intrinsically disordered, oxidatively damaged, or misfolded proteins, factors pivotal in neurodegenerative diseases like Alzheimer’s and Parkinson’s. In our mouse model experiment, ketamine administration notably altered brain synaptic protein profiles within two hours, significantly downregulating proteins strongly associated with Alzheimer’s and Parkinson’s diseases. Furthermore, the altered proteins exhibited enrichment in terms related to plasticity and potentiation, including retrograde endocannabinoid signaling—a pivotal pathway in both short- and long-term plasticity that may elucidate the long-lasting effects of ketamine in major depression. Via the ubiquitin-independent 20S proteasome pathway (UIPS), these drugs maintain cellular protein homeostasis, which is crucial as proteasome activity declines with age, leading to protein aggregation and disease symptoms. Therefore, these findings hold promise for new treatment options not only for brain diseases but also for other systemic conditions associated with unfolded or misfolded proteins.